Arthroscope-assisted reduction of humeral head impression fracture: a case report. Issue 11 (26th November 2022) - Kachi, Takuma; Shitara, Hitoshi; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Hamano, Noritaka; Chikuda, Hirotaka
Abstract: We experienced a case of humeral head impression fracture accounting for approximately 20% of the anterior articular surface. Open reduction and internal fixation of the proximal humeral fracture combined with arthroscope-assisted reduction and internal fixation of the humeral head impression fracture were performed, and good clinical and radiographic outcomes were obtained. Untreated impression fracture may be a potential risk for subluxation or osteoarthritis. However, our arthroscopic approach is minimally invasive and allows for the prevention of these risks.